2022
DOI: 10.1038/s42003-022-03085-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analyses explain Pea KAI2 receptor diversity and reveal stereoselective catalysis during signal perception

Abstract: KAI2 proteins are plant α/β hydrolase receptors which perceive smoke-derived butenolide signals and endogenous, yet unidentified KAI2-ligands (KLs). The number of functional KAI2 receptors varies among species and KAI2 gene duplication and sub-functionalization likely plays an adaptative role by altering specificity towards different KLs. Legumes represent one of the largest families of flowering plants and contain many agronomic crops. Prior to their diversification, KAI2 underwent duplication resulting in KA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 87 publications
2
38
0
Order By: Relevance
“…Villaécija-Aguilar et al 58 reported that root hair development in d14 is still responsive to 5DS 58 , suggesting a D14 -independent strigolactone receptor. D14L paralogs in pea are able to bind 5DS in vitro and hydrolyse strigolactone-like molecules 59 , raising the possibility that strigolactones or strigolactone-derived molecules 60 may bind and activate D14L.…”
Section: Discussionmentioning
confidence: 99%
“…Villaécija-Aguilar et al 58 reported that root hair development in d14 is still responsive to 5DS 58 , suggesting a D14 -independent strigolactone receptor. D14L paralogs in pea are able to bind 5DS in vitro and hydrolyse strigolactone-like molecules 59 , raising the possibility that strigolactones or strigolactone-derived molecules 60 may bind and activate D14L.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we present the crystal structure of A. thaliana DLK2, which, as a major difference to its paralogs AtD14 and AtKAI2, features a significantly smaller substrate binding pocket. Previous structures of strigolactone receptors or KAI2 clade proteins have shown that not only the substitution of amino acids inside the substrate binding pocket determines its size or ligand specificity (Guercio et al, 2022 ; Toh et al, 2015 ) but that also interactions between residues located in different secondary structure elements can influence the volume and shape of the pocket. This has been observed in a hydrogen bond between helices αD1 and αD3 in hyposensitive to light proteins from Striga hermonthica (ShHTL) (Xu et al, 2018 ) and in a loop region between helices αE and αF in KAI2‐like proteins from Physcomitrium patens (Bürger et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, D14 receptors preferentially perceive SLs where the D ring is in 2 0 R configuration (Fig. 1), whilst KAI2 receptors prefer the 2 0 S configuration (Scaffidi et al 2014;de Saint Germain et al 2016;Carbonnel et al 2020;de Saint Germain et al 2021;Guercio et al 2022). Even within D14 and KAI2 families, these receptors have acquired adaptive sensitivity to different species and/or context-specific SLs, allowing these receptors to represent a wider diversity of ligand specificities.…”
Section: Identification Of Strigolactone Receptorsmentioning
confidence: 99%